A Small Molecule Inhibits Protein Disulfide Isomerase and Triggers the Chemosensitization of Cancer Cells1. Issue 47 (26th September 2014) - Eirich, Jürgen; Braig, Simone; Schyschka, Liliana; Servatius, Phil; Hoffmann, Judith; Hecht, Sabrina; Fulda, Simone; Zahler, Stefan; Antes, Iris; Kazmaier, Uli; Sieber, Stephan A.; Vollmar, Angelika M.
Abstract Resistance to chemotherapeutic agents represents a major challenge in cancer research. One approach to this problem is combination therapy, the application of a toxic chemotherapeutic drug together with a sensitizing compound that addresses the vulnerability of cancer cells to induce apoptosis. Here we report the discovery of a new compound class (T8) that sensitizes various cancer cells towards etoposide treatment at subtoxic concentrations. Proteomic analysis revealed protein disulfide isomerase (PDI) as the target of the T8 class. In‐depth chemical and biological studies such as the synthesis of optimized compounds, molecular docking analyses, cellular imaging, and apoptosis assays confirmed the unique mode of action through reversible PDI inhibition.